Age-Related Olfactory Decline Is Associated With Levels of Exercise and Non-exercise Physical Activities - Sollai, Giorgia; Crnjar, Roberto (Frontiers in Aging Neuroscience, 2021)
Objective: This cross-sectional study evaluates the impact of active or non-active lifestyle in terms of physical, cognitive and social activity on the olfactory function in Elderly Subjects (ES) and aims at looking for a correlation between the time devoted to life activities and the score obtained during the olfactory tests by each individual. Methods: One hundred and twenty-two elderly volunteers were recruited in Sardinia (Italy) and divided into active ES (n = 60; 17 men, 43 women; age 67.8 ± 1.12 years) and inactive ES (n = 62; 21 men, 41 women, age 71.1 ± 1.14 years) based on their daily physical activities. The olfactory function was evaluated using the “Sniffin’s Sticks” battery test, while the assessment of daily activities was made by means of personal interviews. Results: A significant effect of active or inactive lifestyle was found on the olfactory function of ES (F(1,120) > 10.16; p < 0.005). A positive correlation was found between the olfactory scores and the number of hours per week dedicated to physical activities (Pearson’s r > 0.32, p ≤ 0.014) in both active and inactive ES. Conclusions: High levels of exercise and non-exercise physical activity are strongly associated with the olfactory function and, consequently, with the quality of life of the elderly. Given the limited physical exercise of elderly people, they can benefit from a more active lifestyle by increasing non-exercise physical activities.